Entropy generation minimization on electromagnetohydrodynamic radiative Casson nanofluid flow over a melting Riga plate - Obalalu, A.M. (John Wiley and Sons Inc, 2022)
Minimizing entropy generation is a technique that helps improve the effectiveness of real processes by studying the associated irreversibility of system performance of nanofluid. This study examines the entropy generation analysis of electromagnetohydrodynamic radiative Casson flow induced by a stretching Riga plate in a non-Darcian porous medium under the influence of internal energy change, Arrhenius activation energy, chemical reaction, and melting heat transfer. The thermophysical features of the fluid are assumed constant in most of the literature. However, this current research bridges this gap by considering viscosity, conductivity, and diffusivity as temperature-dependent variables. Also, the exponential decaying Grinberg term is used as a resistive force in this investigation due to the electromagnetic properties of the Riga plate in the momentum conservation equation. Some suitable dimensionless variables are introduced to remodel the transport equations into unitless ones and then solved numerically by employing Galerkin Weighted Residual Method. Analyses reveal that the Casson parameter declines the fluid velocity, while the existence of the melting parameter has the opposite effect. Also, this article includes some future recommendations. Â© 2022 Wiley Periodicals LLC